2010
DOI: 10.1001/archinternmed.2010.63
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Measures, Body Mass Index, and Pancreatic Cancer

Abstract: Background Pooled data were analyzed from the NCI Pancreatic Cancer Cohort Consortium (PanScan) to study the association between pre-diagnostic anthropometric measures and risk of pancreatic cancer. Methods PanScan applied a nested case-control study design and included 2,170 cases and 2,209 controls. Odds ratios (OR) and 95% confidence intervals (CI) were estimated using unconditional logistic regression for cohort-specific quartiles of body mass index (BMI), weight, height, waist circumference, and waist-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
105
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(125 citation statements)
references
References 57 publications
4
105
2
1
Order By: Relevance
“…This last study also found that centralized fat distribution may increase pancreatic cancer risk, especially in women [49] . Another recent study found that overweight or obesity during early adulthood was associated with a greater risk of pancreatic cancer and a younger age of disease onset (2-6 years earlier than the average age of onset of pancreatic cancer) [50] .…”
Section: Obesitysupporting
confidence: 53%
See 1 more Smart Citation
“…This last study also found that centralized fat distribution may increase pancreatic cancer risk, especially in women [49] . Another recent study found that overweight or obesity during early adulthood was associated with a greater risk of pancreatic cancer and a younger age of disease onset (2-6 years earlier than the average age of onset of pancreatic cancer) [50] .…”
Section: Obesitysupporting
confidence: 53%
“…In a subsequent pooled analysis of data from 13 prospective cohort studies as part of the PANSCAN consortium, overweight and obesity were significantly associated with a 20% excess risk of pancreatic cancer [49] . This last study also found that centralized fat distribution may increase pancreatic cancer risk, especially in women [49] .…”
Section: Obesitymentioning
confidence: 99%
“…As mentioned, several studies present results showing an increased risk of pancreatic cancer with increasing BMI,13, 21, 22, 23 which has not been observed in the MDCS, neither in men nor in women 42. Still, adipose tissue is also known to produce estrogens, thus suggesting it may play a protective role as well.…”
Section: Discussionmentioning
confidence: 93%
“…Tobacco smoking,4, 5, 6 high age4, 7, 8 and heredity9, 10 seem to be the only truly validated risk factors for pancreatic cancer. Several other risk factors have been investigated, and numerous studies claim a significant impact of diabetes,11, 12, 13 pancreatitis,14, 15, 16 alcohol17, 18, 19, 20 and body mass index (BMI)13, 21, 22, 23; however, no consensus has yet been reached.…”
mentioning
confidence: 99%
“…In a large casecontrol study, Silverman et al (6) showed obesity portends a 50-60% increased risk of PDAC in both men and women. Similarly, a pooled case-control analysis using data from the Pancreatic Cancer Cohort Consortium (PanScan) comparing 2170 PDAC cases to 2209 controls showed a positive association between increasing body mass index (BMI) and risk of PDAC [adjusted odds ratio (aOR) for the highest vs. lowest BMI quartile=1.33, 95% confidence interval (CI)= 1.12-1.58, p<0.001 (7).…”
mentioning
confidence: 99%